Video review of family medicine resident clinical encounters: a tool for building emotional intelligence - Koehler, Aubry N.; Knudson, Mark P.; Ballard, Parissa J.; Nicolotti, Linda M.; Caballero-Quinones, Elimarie; Daniel, Stephanie S. (Frontiers in Psychology, 2023)
Video Review (VR) is a well established educational tool for developing the practice of patient-centered care in family medicine residents. There are a number of behaviorally-based checklists that can be use in both live observation as well as VR of clinical encounters to identify and promote behaviors associated with patient-centered care, most of which also overlap with behaviors associated with Emotional Intelligence (EI). We propose a VR that is structured less on a seek-and-find of clinician behaviors and more as a self-reflective exercise of how the clinician presents in the room alongside how they were feeling during that encounter. We believe that this exercise promotes the first two skills of EI (self-awareness and self-management) and then provides a foundation on which to build the second pair of skills (social awareness and relationship management). This perspective paper offers guidance, including stepwise instruction, on how to facilitate such a VR curriculum.